Identification of proteins that can participate in the recruitment of Ttk69 to genomic sites of Drosophila melanogaster - I. S. Osadchiy; T. N. Fedorova; P. G. Georgiev; O. G. Maksimenko (Вавиловский журнал генетики и селекции)
The proteins with the BTB domain play an important role in the processes of activation and repression of transcription. Interestingly, BTB-containing proteins are widely distributed only among higher eukaryotes. Many BTB-containing proteins are transcriptional factors involved in a wide range of developmental processes. One of the key regulators of early development is the BTB-containing protein Ttk (tramtrack), which is able to interact with the Drosophila nucleosome remodeling and histone deacetylation (dNuRD) complex. Ttk69 directly interacts with two protein components of the dNuRD complex, dMi-2 and MEP1. It can be assumed that Ttk69 represses some target genes by remodeling chromatin structure through the recruitment of the dNuRD complex. However, it is still unknown what provides for specific recruitment of Ttk to chromatin in the process of negative/positive regulation of a target gene expression. Although Ttk69 has DNA-binding activity, no extended specific motif has been identified. The purpose of this study was to find proteins that can participate in the recruitment of Ttk to regulatory elements. To identify Ttk partner proteins, screening in the yeast two-hybrid system was performed against a collection of proteins with clusters of C2H2 domains, which bind effectively and specifically to sites on chromatin. As a results, the CG10321 and CG1792 proteins were identified as potential DNA-binding partners of Ttk. We suppose that the CG10321 and CG1792 proteins provide specificity for the recruitment of Ttk and, as a result, of the NuRD-complex to the genome regulatory elements. We found that the Ttk protein is able to interact with the MEP1 and ZnF proteins at once.